Pendampingan Penyusunan Kurikulum Perguruan Tinggi pada Yayasan Pendidikan GUSDURian Banyumas - Shadu Satwika Wijaya; Mujib Mujib (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Since 2019 the Banyumas GUSDURian Education Foundation is in the process of establishing a New Private College in the Banyumas Regency. This step was taken by establishing the Higher Education Management Agency (BPPT) at the Piguramas Foundation. This activity aims to help the Piguramas foundation develop a curriculum that is in line with the Independent Learning-Independent Campus policy. This mentoring activity was carried out using the Focus Group Discussion (FGD) method and peer debriefing. The achievement of this activity is that the Independent Learning-Independence Campus curriculum has been compiled for study programs in local government administration, digital business, and tax management, and policy.